Riding the creative rollercoaster : how leaders evoke creativity, productivity and innovation - Udall, Nick. (Kogan Page, 2014)
"Leadership is about creating opportunities for teams, functions, organizations, and even ecosystems of organizations, to catalyze innovation at all levels. This pioneering book shows leaders how to build cultures of innovation and develop breakthrough strategies through the power of creative teams and evocative leadership. It will help leaders develop the capacity and voltage needed to lead their teams through the highs and lows of the creative process, or the 'creative roller coaster', and release the powerful creative potential of teams and organizations. Rewriting the rules of innovation, each chapter reveals a different part of the puzzle, giving the reader a rich tapestry of new insights to re-order and re-pattern what leadership in today's world can achieve"--